The Penology of Islamic Criminal Law: Reintroduction of Islamic Penology - Candra, Marli (Universitas Islam Negeri Raden Intan Lampung, 2018)
The justification for punishment is an interesting topic and undying debate among the scholars. Those who in favor of traditional approach would state that punishment is retributive in nature, whereas the opposite party would declare that punishment is for future benefits either particularly for offender or society in general. In this article, the researcher will elaborate the penological approach of punishment in Islamic criminal law. This study applies a comparative analysis based on the qualitative approach to compare the concept of punishment and its justification in the modern penology as well as in Islamic perspective. The study finds out that the justification for punishment in Islam, which is mainly contained in the hudûd and qishâsh offenses, does not deviate from what is understood by modern penology. Islamic law provides harsher punishment for serious offenses, but at the same time, it also prescribes ways on how to reduce such punishments.